A historical controlled study of domestic trastuzumab and pertuzumab in combination with docetaxel for the neoadjuvant treatment of early HER2-positive breast cancer - Xu, Dongdong; Wu, Jiang; Yu, Jing; Yang, Yuqing; Wen, Xinxin; Yang, Jixin; Wei, Hongliang; Xu, Xiaolong; Li, Yike; Yang, Liu; Wang, Lei; Wang, Yijia; et al. (Frontiers in Oncology, 2024)
Background HER2-positive molecular breast cancer subtypes are characterized by high aggressiveness and malignancy, and their metastasis and mortality rates are among the highest of all types of breast cancer. The use of anti-HER2-targeted agents in neoadjuvant therapy has significantly improved the prognosis of patients with HER2-positive breast cancer. In this study, we investigated the efficacy and safety of a neoadjuvant Chinese THP regimen (docetaxel, trastuzumab biosimilar TQB211 plus the pertuzumab biosimilar TQB2440 or pertuzumab) for ER/PR-negative and HER2-positive breast cancer in China. Method All enrolled patients received the THP regimen (T: docetaxel 75 mg/m2 per cycle; H: trastuzumab biosimilar TQB211 8 mg/kg in the first cycle and 6 mg/kg maintenance dose in cycles 2 to 4; P: pertuzumab biosimilar TQB2440 or pertuzumab 840 mg in the first cycle, maintenance dose 420 mg in cycles 2 to 4) every 3 weeks for 4 cycles. The biosimilar TQB2440 pertuzumab and pertuzumab were randomly assigned to patients. Docetaxel, TQB211, and TQB2440 were all developed by Chiatai Tianqing. The primary endpoint was the complete pathological response (pCR) in the breast, and the secondary endpoint was cardiac safety. Results Of the 28 eligible patients, 19 (67.9%) achieved tpCR. The tpCR rate was higher than in the NeoSphere trial (pCR63.2%) and the PEONY study (tpCR52.5%). The adverse events that occurred most frequently were leukopenia and neutropenia, with incidence rates of 82.1% and 75.0%, respectively. Of these, grade 3 leukopenia and neutropenia occupied 46.4% and 35.7%. Other grade 3 or higher adverse events were bone marrow suppression (7.1%), lymphopenia (3.6%), and anemia (3.6%). There were no events of heart failure in patients and no patient died during the neoadjuvant phase. Conclusion Domestic dual-target HP has a more satisfactory efficacy and safety in the neoadjuvant phase of treatment. Clinical trial registration https://clinicaltrials.gov/study/NCT05985187, NCT05985187.